Higher Civil Servants in Postwar Japan : Their Social Origins, Educational Backgrounds, and Career Patterns - Kubota, Akira (Princeton, NJ : Princeton University Press, 2015)
This volume presents an analysis of Japan's powerful upper bureaucracy in the post-war period. The author's aim is to provide an empirical foundation for the many impressionistic accounts of Japanese bureaucracy and a systematic basis for comparative studies of bureaucracies in other countries. The study ranges from the family and geographic backgrounds of higher civil servants through their educational training and career patterns to their retirement and post-retirement activities. Throughout, the emphasis is on assembling and analyzing the kind of systematic data that provide a solid basis for understanding how the Japanese bureaucracy actually works.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Foreword -- Acknowledgments -- Contents -- Tables -- 1. Introduction -- 2. Scope and Method of Study -- 3. Social Origins -- 4. Educational Backgrounds -- 5. Career Patterns -- 6. Retirement -- 7. The Postwar Japanese Bureaucracy -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Bureaucracy; Government executives -- Japan; World War, 1939-1945 -- Influence; POLITICAL SCIENCE / General